Creation of service permanent establishment in Russian Federation when providing R&D services by foreign specialists - E. A. Zakharov (Правоприменение, 2021)
The subject. The author examines the criteria of creation of service permanent establishment (PE) in Russia and possibility of creation of this type of PE in providing R&D services in Russia by foreign specialists.The aim of the paper is to confirm or refute the hypothesis that the provision of R&D ser-vices by foreign specialists in Russia creates a service permanent establishment. The author also analyzes the current science legislation of Russia and suggests ways of its improvement to reduce tax risks.The methodology. The author used general scientific dialectical method of scientific knowledge, the formal-logical method, in particular analysis and synthesis in examining criteria of creation of service permanent establishment. The author also uses a systematic method and a simulation method to establish the relationship between the science legislation and tax legislation.The main results. The activity of foreign scientific specialists in Russia potentially originates the risk of creation of a permanent establishment on the territory of the Russia for the foreign organization, which sent that specialist to provide the relevant services. However, when comparing the international and domestic law enforcement approach, the author revealed a feature of the latter, which consists in applying the criteria of the physical type of permanent establishment to a service permanent establishment, which in turn gives rise to legal uncertainty and the risk of double taxation in some situations. There is no relevant judicial practice on the topic. Budgetary scientific organizations have a certain priority over commercial scientific organizations when involving foreign specialists in R&D activities in Russia.Conclusions. The criteria for the creation of service permanent establishment (including the provision of R&D services) in domestic practice have an ambiguous, evaluative interpretation. However, the risks of discretion in assessing the criteria for creation of service permanent establishment can be eliminated by clarifying these criteria in the Tax Code of the Russian Federation. Amendments to the science legislation can also eliminate above and fore-going risks.